Co‐Assembly between Fmoc Diphenylalanine and Diphenylalanine within a 3D Fibrous Viscous Network Confers Atypical Curvature and Branching. (15th October 2020) - Chakraborty, Priyadarshi; Tang, Yiming; Guterman, Tom; Arnon, Zohar A.; Yao, Yifei; Wei, Guanghong; Gazit, Ehud
Abstract: Supramolecular polymer co‐assembly is a useful approach to modulate peptide nanostructures. However, the co‐assembly scenario where one of the peptide building blocks simultaneously forms a hydrogel is yet to be studied. Herein, we investigate the co‐assembly formation of diphenylalanine (FF), and Fmoc‐diphenylalanine (FmocFF) within the 3D network of FmocFF hydrogel. The overlapping peptide sequence between the two building blocks leads to their co‐assembly within the gel state modulating the nature of the FF crystals. We observe the formation of branched microcrystalline aggregates with an atypical curvature, in contrast to the FF assemblies obtained from aqueous solution. Optical microscopy reveal the sigmoidal kinetic growth profile of these aggregates. Microfluidics and ToF‐SIMS experiments exhibit the presence of co‐assembled structures of FF and FmocFF in the crystalline aggregates. Molecular dynamics simulation was used to decipher the mechanism of co‐assembly formation. Abstract : Supramolecular polymer co‐assembly between diphenylalanine and Fmoc‐diphenylalanine yields branched and curled amyloidogenic aggregates within 3D network of hydrogels, unlike the linear crystalline aggregates obtained from an aqueous solution of diphenylalanine. Theoretical and experimental studies prove the existence of co‐assembly between the dipeptide and hydrogelator in the amyloidogenic crystalline aggregates.